Enhanced ATM Security with OTP Based Authentication - Prashant Kumar Yadav, Akhtar Husain, Surjeet Kumar (International Journal of Advanced Science and Technology, 2020)
This research article is proposed to enhance the security of traditional ATM machine. We are introducing a new technique that enhances the overall mechanism, security, and comfort of the ATM transactions. Biometric information such as face recognition or finger print detection and OTP (One-TimePassword) may be used for enhancing the security of ATM transactions as well as user’s private information. Biometric authentication technique helpsa machine (biometrically enhanced) to recognize an individual user independently and uniquely. So we can introduce the face or thumb impression as a security key. This new security key can totally avoid bank fraudsdue to compromised security of ATM and bank account related information. On the other hand, one time password (OTP) will help the user as they need not to remember the password or security pin of ATM.